Reduced Social Network Drinking is Associated with Improved Response Inhibition in Women During Early Recovery from Alcohol Use Disorders: A Pilot Study. - McCutcheon, Vivia V.; Luke, Douglas A.; Lessov ‐ Schlaggar, Christina N. (Alcoholism: Clinical & Experimental Research, 2016)
Background Social support for recovery from alcohol use disorders ( AUDs) is associated with improvements in self-reported impulsive behavior in individuals treated for AUDs. We build on these findings using a behavioral task-based measure of response inhibition, a well-defined component of impulsivity, to examine the association of disinhibition with alcohol-specific social network characteristics during early recovery. Methods Women ( n = 28) were recruited from treatment for AUD within 3 to 4 weeks of their last drink and were assessed at baseline and again 3 months later. Outcome measures were level of disinhibition at baseline and change in disinhibition from baseline to follow-up, measured using a computer-based continuous performance test. The primary independent variables were level of drinking in the social network at baseline and change in network drinking from baseline to follow-up. Results The sample [50% black, age M ( SD) = 42.3 (9.5)] reported high rates of physical and sexual abuse before age 13 (43%), psychiatric disorder (71%), drug use disorder (78%), and previous treatment (71%). More drinking in participants' social networks was associated with greater disinhibition at baseline ( β = 12.5, 95% CI = 6.3, 18.7). A reduction in network drinking from baseline to follow-up was associated with reduced disinhibition ( β = −6.0, 95% CI = −11.3, −0.78) independent of IQ, recent alcohol consumption, and self-reported negative urgency. Conclusions This study extends previous findings of an association between social networks and self-reported impulsivity to a neurobehavioral phenotype, response inhibition, suggesting that abstinence-supporting social networks may play a role in cognitive change during early recovery from AUDs.